Menschenrechte in den Zeiten der Globalisierung - Bogacz, Daniel (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
The core question of this article, around which the narrative is centered, concerns current issues connected with fulfilling international human rights guarantees – in particular the right to life and the related right to food. Despite numerous initiatives undertaken by the highly developed countries of the wealthy so-called Global North to aid the impoverished societies of the so-called Global South, the widespread phenomena of hunger and underdevelopment have not been significantly reduced. Deep socioeconomic divisions among respective states and regions lead to exploitation in the area of international relations, which has continued unabated since the beginning of the early modern period. This is evident especially in the context of economic relations on the example of the international coffee trade. Even if, through their social and economic systems, highly developed countries manage to successfully pursue a policy of social diversity management towards achieving the goals of economic growth, reducing drastic social disparities, satisfying social justice, and respecting the fundamental rights of the individual – in the realities of the global free market deep social disparities among contracting parties facilitate exploitative practices, result in unequal trade, and perpetuate colonial relationships between highly developed and developing nations. By the same token, the global free market resembles the pre-social-contract state of nature in which unfettered freedom denotes arbitrariness – unacceptable in highly developed economies – leading to commonplace human rights violations. In the above-mentioned situation some form of intervention designed to create a level playing field on the global market appears necessary in order to ensure the protection of socially weak parties against abuses by stronger market players. Only fulfilling this condition will pave the way for an effective policy of economic development and the general application of the principle of fair trade
Keywords: human rights; social justice; right to food; globalization; underdevelopment; development policy; fair trade; coffee busines; development aid; imperialism theory; social diversity